'I Believe in That Version of the Future'. Cli-Fi and Design Fictions as Dialogical Frameworks for Expert Engagements. (28th July 2017) - Reitsma, Lizette; Wessman, Stina; Önnevall, Elin
Abstract: The Design for Sustainability community has highlighted the importance of engaging different societal stakeholders and experts in discussions of how to achieve sustainability. The work we present is situated within a research project exploring 'How climate goals can be portrayed to explore individual's' carbon footprint'. In this paper we present a dialogical tool to engage experts in the discussion of issues related to moral, ethical and societal aspects in the transition towards a low emission society. We created two stories that were used during a workshop with experts. Those stories are positioned within the Climate Fiction genre, which centres on man-made climate change. We shaped the stories as Design Fictions, a design approach focusing on sparking discussions and explore possible worlds. The stories facilitated discussions on the aspects that we aimed for. We see potential in this approach to facilitate expert involvement and we highlight opportunities and improvement-potential.